Patient‐reported outcomes following neoadjuvant endocrine therapy, external beam radiation, and adjuvant continuous/intermittent endocrine therapy for locally advanced prostate cancer: A randomized phase III trial. (1st May 2021) - Yokomizo, Akira; Koga, Hirofumi; Ito, Kazuto; Takezawa, Yutaka; Komiyama, Motokiyo; Nishimura, Kazuo; Yonese, Junji; Hashine, Katsuyoshi; Masumori, Naoya; Arai, Gaku; Saito, Shiro; Shinohara, Mitsuru; et al.
Abstract: Background: We evaluated patient‐reported outcomes (PRO) during neoadjuvant androgen deprivation therapy (ADT) plus external beam radiation therapy (EBRT) followed by either adjuvant continuous ADT (CADT) or intermittent ADT (IADT) for patients with locally advanced prostate cancer (Pca). Methods: A multicenter, randomized phase III trial enrolled 303 patients with locally advanced Pca. The patients were treated with 6 months (M) of ADT followed by 72 Gy of EBRT, and were randomly assigned to CADT or IADT after 14 M. The PROs were evaluated at sic points: baseline, 6 M, 8 M, 14 M, 20 M, and 38 M using FACT‐P questionnaires and EPIC urinary, bowel, and sexual bother subscales. Results: The FACT‐P total scores were significantly better ( p  < 0.05) in IADT versus CADT at 20 M (121.6 vs.115.4) and at 38 M (119.9 vs. 115.2). The physical well‐being scores (PWB) were significantly better ( p  < 0.05) in IADT versus CADT at 38 M (25.4 vs. 24.0). The functional scores were significantly better in IADT than those in CADT at 14 M (20.2 vs18.7, p  < 0.05) and at 20 M (21.0 vs.18.9, p  < 0.05). Conclusion: The PRO was significantly favorable in IADT on FACT‐P total score at 20 M and 38 M, PWB and functional scores at 38 M. Abstract : The quality of life was significantly favorable in intermittent androgen deprivation therapy (ADT) on FACT‐P total score, physical well‐being and functional score than those is continuous ADT in adjuvant hormone therapy for locally advanced prostate cancer.